Lateral patellar tilting can also result in cartilage lesions of tibial plateau - the characteristic features of excessive lateral pressure syndrome: a retrospective study of 141 cases - Li Minghao; Liu Qiang; Cui Guoqing (BMC Musculoskeletal Disorders)
Abstract Background To comprehensively summarize the characteristics of cartilage and other knee joint lesions associated with excessive lateral pressure syndrome (ELPS). Methods Patients diagnosed with ELPS and admitted to our department between October 1, 2015, and September 30, 2023 were retrospectively included in this study. Prior to undergoing arthroscopic examination and surgery, all included patients underwent knee MRI evaluation. The lesion regions and corresponding lesion grading of each knee joint were meticulously documented, and the concordance between imaging and arthroscopic evaluation was quantified. All patients were categorized based on age and gender, and further comparison of each group was made. Results There were 82 male participants and 59 female participants included. No significant differences in age or side distribution were observed. Regarding gender comparison, there were no statistically significant differences in imaging observations (P = 0.940) and arthroscopic examinations (P = 0.237). There were no significant differences observed in radiographic incidences among all three groups divided by age, while during arthroscopic examination, a significantly higher incidence was found in over 50 group compared to both those under 20 and those aged between 20 and 50. The incidence of Graded that both radiographic evaluation and arthroscopic observation demonstrated a significantly higher incidence in the > 50 years old group compared to the other two groups. Conclusions In addition to patellofemoral joint cartilage lesions, excessive lateral pressure syndrome (ELPS) of the patella can also cause cartilage lesions in the central region of the medial tibial plateau and posterior region of the lateral tibial plateau. These specific sites of lesion are not influenced by gender or age. The incidence of full-thickness cartilage defects gradually increases with age. Trial registration The Ethics Committee of the Third Hospital of Peking University approved this study. (No.: IRB00006761-M2021002) Level of evidence IV Case series.